Recovery method for recovering cobalt and nickel

JP2026166362APending Publication Date: 2026-10-14DOWA ECO SYST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059246
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0009】 本発明によると、溶媒抽出法を用いずに、コバルト、ニッケル、及び銅を含む原料粉から、銅の混入を抑制しつつ、高効率でコバルト及びニッケルを回収することができる回収方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166362000002
    Figure 2026166362000002
  • Figure 2026166362000003
    Figure 2026166362000003
  • Figure 2026166362000004
    Figure 2026166362000004
Patent Text Reader

Abstract

To provide a recovery method that can recover cobalt and nickel from raw material powders containing cobalt, nickel, and copper with high efficiency while suppressing copper contamination, without using solvent extraction methods. [Solution] A recovery method for recovering cobalt and nickel from raw material powder containing cobalt, nickel and copper, comprising: an acid leaching step of mixing a slurry containing raw material powder containing cobalt, nickel and copper and water with an acid to obtain an acid leaching solution; a pyrophosphate mixing step of mixing the acid leaching solution obtained in the acid leaching step with a water-soluble pyrophosphate compound to obtain a pyrophosphate mixture solution; and a solid-liquid separation step of performing solid-liquid separation on the pyrophosphate mixture solution obtained in the pyrophosphate mixing step to obtain an aqueous solution containing cobalt and nickel.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a recovery method for recovering cobalt and nickel from a raw material powder containing cobalt, nickel, and copper.

BACKGROUND ART

[0002] Lithium-ion secondary batteries and the like contain valuable materials such as cobalt and nickel, so in recent years, recycling of these valuable materials from powder obtained by crushing and incinerating lithium-ion secondary batteries and the like has attracted attention.

[0003] Patent Document 1 describes a metal recovery method for lithium-ion battery waste, which includes a wet treatment by a so-called solvent extraction method, in which metals in lithium-ion battery waste are leached with an acid, and the metals are extracted from a metal-containing solution in which the metals are dissolved.

PRIOR ART DOCUMENTS

PATENT DOCUMENTS

[0004]

PATENT DOCUMENT 1

SUMMARY OF THE INVENTION

PROBLEM TO BE SOLVED BY THE INVENTION

[0005] In recent years, in recycling cobalt and nickel contained in lithium-ion batteries, recovery of cobalt and nickel with few impurities such as copper has been studied. The solvent extraction method described in Patent Document 1 is a widely used technique for recovering cobalt and nickel with few impurities at a high yield, but has disadvantages such as the requirement of a special solvent which increases cost, and high cost and high energy consumption for disposal of the used solvent, and a method for recovering cobalt and nickel without using a solvent extraction method has been demanded. Therefore, after diligent research by the inventors, we discovered that by mixing an acid leachate with a water-soluble pyrophosphate compound, the recovery rates of cobalt and nickel can be maintained at a high level without using solvent extraction, while the contamination of copper can be reduced, thus completing the present invention.

[0006] The present invention aims to solve the aforementioned problems in the conventional approach and achieve the following objectives. Specifically, the present invention aims to provide a recovery method that can recover cobalt and nickel from raw material powders containing cobalt, nickel, and copper with high efficiency while suppressing the inclusion of copper, without using solvent extraction methods. [Means for solving the problem]

[0007] As a result of diligent research conducted by the present inventors to achieve the above objective, they have discovered that it is possible to provide a recovery method that can recover cobalt and nickel from raw material powders containing cobalt, nickel, and copper with high efficiency while suppressing the inclusion of copper, without using solvent extraction methods.

[0008] The present invention is based on the aforementioned findings by the inventors, and the means for solving the aforementioned problems are as follows: <1> A recovery method for recovering cobalt and nickel from raw material powder containing cobalt, nickel, and copper, An acid leaching process involves mixing a slurry containing cobalt, nickel, and copper raw material powders and water with an acid to obtain an acid leaching solution. A pyrophosphate mixing step involves mixing the acid leachate obtained in the acid leaching step with a water-soluble pyrophosphate compound to obtain a pyrophosphate mixture. The recovery method is characterized by comprising a solid-liquid separation step, in which the pyrophosphate mixture obtained in the pyrophosphate mixing step is subjected to solid-liquid separation to obtain an aqueous solution containing cobalt and nickel. <2> Prior to the pyrophosphate addition step, the pH of the acid leachate obtained in the acid leaching step is adjusted to be between 2.0 and 7.0. <1> This is the collection method described in [the relevant document]. <3> The raw material powder contains iron, <1> or <2> This is the collection method described in [the relevant document]. <4> The oxidation-reduction potential of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step is adjusted to be between 0mV and 600mV, measured with reference to a silver-silver chloride electrode. <3> This is the collection method described in [the relevant document]. <5> The raw material powder contains at least one of aluminum and zinc, <1> or <2> This is the collection method described in [the relevant document]. <6> The pH of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step is adjusted to be between 2.0 and 7.0. <5> This is the collection method described in [the relevant document]. <7> In the acid leaching step, phosphoric acid is added after mixing the slurry with the acid to obtain the acid leaching solution. <5> This is the collection method described in [the relevant document]. <8> The raw material powder is a magnetic material obtained by classifying and wet magnetic separation of heat-treated lithium-ion secondary battery materials. <1> or <2> This is the collection method described in [the relevant document]. <9> The acid leaching process is carried out under the condition that the oxidation-reduction potential measured with respect to the silver-silver chloride electrode is between -300mV and 0mV. <1> or <2> The collection method described below. [Effects of the Invention]

[0009] According to the present invention, a recovery method is provided that can recover cobalt and nickel from raw material powder containing cobalt, nickel, and copper with high efficiency while suppressing the inclusion of copper, without using solvent extraction methods. [Brief explanation of the drawing]

[0010] [Figure 1] Figure 1 is a schematic diagram showing an example of a drum-type wet magnetic separator. [Figure 2] Figure 2 is a schematic diagram showing another example of a drum-type wet magnetic separator. [Figure 3A] Figure 3A is a diagram showing an example of a horizontal matrix. [Figure 3B] Figure 3B is a diagram showing an example of a vertical matrix. [Figure 4] Figure 4 is a drawing showing an example of a matrix member in which three horizontal matrices and four vertical matrices are alternately stacked. [Figure 5] Figure 5 is a diagram showing an example of the flow of the recovery method of the present invention. [Figure 6] Figure 6 is a diagram showing another example of the flow of the recovery method of the present invention. [Modes for Carrying Out the Invention]

[0011] (Recovery Method) The recovery method is a recovery method for recovering cobalt and nickel from a raw material powder containing cobalt, nickel, and copper. The recovery method includes an acid leaching step, a pyrophosphoric acid mixing step, and a solid-liquid separation step, and may further include other steps.

[0012] -Acid Leaching Step- The acid leaching step is a step of mixing a slurry containing water and a raw material powder containing cobalt, nickel and copper with an acid to obtain an acid leachate.

[0013] The mixing method in the acid leaching step is not particularly limited and may be appropriately selected according to the purpose, and examples thereof include a method of adding the acid to the slurry containing water and the raw material powder containing cobalt, nickel and copper, and a method of mixing the raw material powder with an aqueous acid solution such as sulfuric acid. The mixing may be addition. In addition to the addition, stirring may be performed, and stirring may be performed while applying ultrasonic waves.

[0014] The slurry containing water and the raw material powder containing cobalt, nickel and copper can be obtained by mixing the raw material powder containing cobalt, nickel and copper with the water. There are no particular restrictions on the method of mixing the raw material powder containing cobalt, nickel, and copper with the water, and a suitable method can be selected depending on the purpose. For example, one method is to add the water to the raw material powder containing cobalt, nickel, and copper. In addition to the above additions, the mixture may be stirred, or stirred while applying ultrasonic waves.

[0015] In the aforementioned acid leaching process, it is preferable to add an oxidizing agent in addition to the acid in order to improve the leaching rate of cobalt and nickel.

[0016] In the acid leaching process described above, phosphoric acid may also be added. The addition of phosphoric acid may be performed before acid leaching, simultaneously with the acid, or after mixing the slurry and the acid (after acid leaching). Among these, it is preferable to perform the addition after mixing the slurry and the acid (after acid leaching) in order to recover cobalt and nickel with high efficiency.

[0017] --Raw material powder-- The aforementioned raw material powder is not particularly limited as long as it contains cobalt, nickel, and copper, and can be appropriately selected depending on the purpose. It may also contain manganese, lithium, iron, aluminum, zinc, and the like. Among these, those containing iron, or at least one of aluminum and zinc, are preferred.

[0018] The raw material powder may be heat-treated material (battery powder) of a lithium-ion secondary battery. Alternatively, it may be material obtained by partially removing components such as molten aluminum from the heat-treated material, or it may be a product recovered by physically separating a lithium-ion secondary battery or its heat-treated material through crushing, classification, magnetic separation, etc. Specifically, the raw material powder may be a magnetic deposit obtained by classifying and wet magnetic separation of heat-treated lithium-ion secondary battery materials. Specific examples of the components of the raw material powder include, for example, those containing 1-20% by mass of cobalt, 5-50% by mass of nickel, 0.1-10% by mass of copper, 0.1-5% by mass of iron, 1-10% by mass of aluminum, and 0.01-1% by mass of zinc.

[0019] There are no particular restrictions on the lithium-ion secondary battery, and it can be appropriately selected depending on the purpose. Examples include defective lithium-ion secondary batteries generated during the manufacturing process, lithium-ion secondary batteries discarded due to malfunctions of the equipment used, the end of the equipment's lifespan, and used lithium-ion secondary batteries discarded due to their lifespan.

[0020] There are no particular restrictions on the shape of the lithium-ion secondary battery, and it can be appropriately selected according to the purpose. Examples include laminated type, cylindrical type, button type, coin type, rectangular type, and flat type.

[0021] There are no particular restrictions on the form of the lithium-ion secondary battery, and it can be appropriately selected according to the purpose. Examples include battery cells, battery modules, and battery packs. The aforementioned battery module refers to a system in which multiple battery cells, which are individual batteries, are connected and assembled into a single enclosure. The aforementioned battery pack refers to a collection of multiple battery modules housed in a single enclosure. The battery pack may also include a control controller or a cooling device.

[0022] There are no particular restrictions on the structure, size, and material of the lithium-ion secondary battery, and they can be appropriately selected according to the purpose.

[0023] Examples of the lithium-ion secondary battery include one comprising a positive electrode, a negative electrode, a separator, an electrolyte solution containing an electrolyte and an organic solvent, and an outer container which is a battery case that houses the positive electrode, negative electrode, separator, and electrolyte solution. It should be noted that the lithium-ion secondary battery may have a detached negative electrode or a detached positive electrode.

[0024] The positive electrode is not particularly limited as long as it has a positive electrode active material containing at least one of cobalt and nickel, and can be appropriately selected depending on the purpose. There are no particular restrictions on the shape of the positive electrode, and it can be appropriately selected according to the purpose, for example, it can be a flat plate or a sheet.

[0025] There are no particular restrictions on the shape, structure, size, or material of the positive electrode current collector, and it can be appropriately selected according to the purpose. The shape of the positive electrode current collector can be, for example, a foil shape. Examples of materials for the positive electrode current collector include stainless steel, nickel, aluminum, copper, titanium, and tantalum. Among these, aluminum is preferred.

[0026] There are no particular restrictions on the cathode material, and it can be appropriately selected according to the purpose. For example, a cathode material that contains at least a lithium-containing cathode active material and optionally a conductive agent and a binder resin can be used.

[0027] The positive electrode active material is not particularly limited as long as it contains at least one of cobalt and nickel, and materials containing manganese, aluminum, iron, titanium, etc., can be appropriately selected depending on the purpose. Examples of the positive electrode active material include lithium manganese oxide (LiMn2O4), referred to as the LMO system; lithium cobalt oxide (LiCoO2), referred to as the LCO system; and LiNi, referred to as the ternary system and the NCM system. x Co y Mn zO2(x+y+z=1), LiNi, which is referred to as the NCA type. x Co y Al z (x+y+z=1), lithium iron phosphate (LiFePO4), lithium cobalt-nickelate (LiCo 1 / 2 Ni 1 / 2 Examples include O2 and lithium titanate (Li2TiO3). These may be used individually or in combination of two or more.

[0028] The conductive agent is not particularly limited and can be appropriately selected depending on the purpose. Examples include carbon black, graphite, carbon fiber, and metal carbides. The binder resin is not particularly limited and can be appropriately selected depending on the purpose. Examples include homopolymers or copolymers of vinylidene fluoride, tetrafluoroethylene, acrylonitrile, ethylene oxide, etc., and styrene-butadiene rubber.

[0029] The aforementioned negative electrode is not particularly limited as long as it has a negative electrode active material, and can be appropriately selected according to the purpose. There are no particular restrictions on the shape of the negative electrode, and it can be appropriately selected according to the purpose, for example, a flat plate shape, a sheet shape, etc.

[0030] There are no particular restrictions on the shape, structure, size, or material of the negative electrode current collector, and it can be appropriately selected according to the purpose. The shape of the negative electrode current collector can be, for example, a foil shape. Examples of materials for the negative electrode current collector include stainless steel, nickel, aluminum, copper, titanium, and tantalum. Among these, copper is preferred.

[0031] There are no particular restrictions on the negative electrode active material, and it can be appropriately selected depending on the purpose. Examples include carbon materials such as graphite and hard carbon, titanate, and silicon. These may be used individually or in combination of two or more.

[0032] The positive electrode current collector and the negative electrode current collector have a laminated structure, and there are no particular restrictions on the laminate; they can be appropriately selected according to the purpose.

[0033] There are no particular restrictions on the material of the outer casing (housing) of the lithium-ion secondary battery, and it can be appropriately selected according to the purpose. Examples include aluminum, iron, stainless steel, and resin (plastic).

[0034] The heat-treated lithium-ion secondary battery mentioned above refers to a product obtained by heat-treating the lithium-ion secondary battery. The heat-treated lithium-ion secondary battery may be a roasted product obtained by roasting a lithium-ion secondary battery.

[0035] There are no particular limitations on the method used for the heat treatment, and it can be appropriately selected depending on the purpose. For example, the heat treatment can be performed by heating the object in a known roasting furnace. There are no particular restrictions on the roasting furnace, and it can be appropriately selected according to the purpose. Examples include rotary kilns, fluidized bed furnaces, tunnel furnaces, batch-type furnaces such as muffle furnaces, cupolas, and stoker furnaces.

[0036] There are no particular restrictions on the atmosphere used for the heat treatment, and it can be appropriately selected according to the purpose. Examples include an air atmosphere, an inert atmosphere, a reducing atmosphere, and a low-oxygen atmosphere.

[0037] The aforementioned atmospheric atmosphere (air atmosphere) refers to an atmosphere using air containing approximately 21% oxygen by volume and approximately 78% nitrogen by volume. The aforementioned inert atmosphere can be exemplified by an atmosphere consisting of nitrogen or argon. The aforementioned reducing atmosphere refers to an atmosphere containing CO, H2, H2S, SO2, etc., in an inert atmosphere such as nitrogen or argon. The aforementioned low-oxygen atmosphere refers to an atmosphere in which the oxygen concentration is 20% by volume or less.

[0038] In the low-oxygen atmosphere, the oxygen concentration is preferably 0% by volume or more and 11% by volume or less, and more preferably 0% by volume or more and 5% by volume or less. By roasting the lithium-ion secondary battery in an atmosphere with an oxygen concentration of 11% by volume or less, the oxidation of valuable metals in the lithium-ion secondary battery can be suppressed. There are no particular restrictions on the method for adjusting the oxygen concentration, and it can be appropriately selected depending on the purpose. Examples include burning a gas burner or kerosene burner at a low air ratio, or using a mixture of an inert gas such as nitrogen or argon with air. Furthermore, roasting under an inert gas atmosphere such as nitrogen or argon (oxygen concentration 0 vol%) is more preferable because it suppresses the oxidation of valuable metals in lithium-ion secondary batteries.

[0039] There are no particular restrictions on the temperature (heat treatment temperature) in the heat treatment described above, and it can be appropriately selected according to the purpose, but it is preferably 400°C to 1,080°C, more preferably 660°C to 1,080°C, and particularly preferably 750°C to 900°C. The heat treatment temperature may be a temperature that is above the melting point of the current collector with the lower melting point among the positive electrode current collector and the negative electrode current collector, and below the melting point of the current collector with the higher melting point.

[0040] The heat treatment temperature refers to the temperature of the lithium-ion secondary battery, which is the object being heat-treated. The heat treatment temperature can be measured by inserting a thermometer, such as a coupler or thermistor, into the object during heat treatment. By setting the heat treatment temperature to 400°C or higher, the cobalt oxide and nickel oxide contained in the positive electrode active material are reduced to metal. Furthermore, these metals can be grown to a particle size that is easily magnetically attached in the subsequent magnetic separation process. This particle size growth is more likely to occur with higher heat treatment temperatures. Furthermore, by setting the heat treatment temperature to 660°C or higher, it becomes possible to melt the aluminum that constitutes the outer casing of the LIB pack and cell, and separate and recover it from other components. Also, by setting the heat treatment temperature to 750°C or higher, the lithium in Li(Ni / Co / Mn)O2 in the positive electrode active material and LiPF6 in the electrolyte can be converted into substances that are soluble in aqueous solutions, such as lithium fluoride (LiF), lithium carbonate (Li2CO3), and lithium oxide (Li2O), which can then be leached into the dispersion medium during the slurrying process.

[0041] It is preferable that the outer casing of the lithium-ion secondary battery is made of a material having a melting point higher than the heat treatment temperature. If the outer casing of the lithium-ion secondary battery is made of a material having a melting point lower than the heat treatment temperature, it is preferable to perform the heat treatment in a low-oxygen atmosphere with an oxygen concentration of 11 volume% or less, or at least in the interior of the lithium-ion secondary battery during roasting (especially the positive electrode current collector and negative electrode current collector located inside the outer casing of the lithium-ion secondary battery) with an oxygen concentration of 11 volume% or less.

[0042] As a method for achieving the low-oxygen atmosphere, for example, the positive or negative electrode of a lithium-ion secondary battery may be placed in an oxygen-shielding container and heat-treated. The material of the oxygen-shielding container is not particularly limited as long as it has a melting point above the heat treatment temperature, and can be appropriately selected according to the purpose. For example, if the heat treatment temperature is 800°C, materials such as iron and stainless steel, which have a melting point higher than this heat treatment temperature, can be used.

[0043] It is preferable to provide an opening in the oxygen shielding container to release the gas pressure of gases generated by combustion of the electrolyte, etc., in the lithium-ion secondary battery or laminate. It is preferable that the opening area of ​​the opening is 12.5% ​​or less of the surface area of ​​the outer container in which the opening is provided. More preferably, the opening area of ​​the opening is 6.3% or less of the surface area of ​​the outer container in which the opening is provided. The aforementioned opening has no particular restrictions on its shape, size, or location, and can be appropriately selected according to the purpose.

[0044] There are no particular restrictions on the time (heat treatment time) in the heat treatment described above, and it can be appropriately selected according to the purpose, but it is preferably between 1 minute and 10 hours, and more preferably between 1 minute and 3 hours. The heat treatment time should be sufficient to reach the desired temperature at which cobalt and nickel undergo metallization, and the holding time should be sufficient to allow time for metallization to progress. Having the heat treatment time within a preferred range is advantageous in terms of the cost of the heat treatment. Therefore, it is preferable to perform the heat treatment at a temperature of 400°C to 1,080°C for at least one hour.

[0045] --water-- There are no particular restrictions on the water mentioned above, and it can be appropriately selected depending on the purpose. Examples include pure water such as industrial water, tap water, ion-exchanged water, ultrafiltered water, reverse osmosis water, and distilled water, as well as ultrapure water. Among these, ion-exchanged water is preferred because it has relatively low manufacturing costs and relatively low impurity concentrations.

[0046] There are no particular restrictions on the amount of water, and it can be appropriately selected depending on the purpose, but it is preferably 100g to 1000g per 100g of raw material powder, more preferably 200g to 800g, and even more preferably 300g to 500g.

[0047] There are no particular restrictions on the solid-liquid ratio (concentration (mass ratio) of raw material powder to water) in the slurry, and it can be appropriately selected according to the purpose, but it is preferably 1% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 40% by mass or less, and even more preferably 20% by mass or more and 30% by mass or less.

[0048] --Acids, oxidizing agents-- The acid is not particularly limited and can be appropriately selected depending on the purpose, but sulfuric acid is preferred.

[0049] There are no particular restrictions on the concentration of sulfuric acid mixed in the acid leaching process, and it can be appropriately selected depending on the purpose, but it is preferably 5% by mass or more and 99% by mass or less, preferably 50% by mass or more and 99% by mass or less, and more preferably 90% by mass or more and 99% by mass or less.

[0050] There are no particular restrictions on the oxidizing agent, and it can be appropriately selected depending on the purpose, but sodium hypochlorite or hydrogen peroxide are preferred in terms of recovering cobalt and nickel with high efficiency. An oxidizing gas can also be used as the oxidizing agent. There are no particular restrictions on the oxidizing gas, and it can be appropriately selected depending on the purpose, for example, air or oxygen.

[0051] There are no particular restrictions on the concentration of sodium hypochlorite mixed in the acid leaching process, and it can be appropriately selected depending on the purpose. However, in terms of recovering cobalt and nickel with high efficiency, a concentration of 5% to 30% by mass is preferred, 10% to 20% by mass is preferred, and 11% to 15% by mass is even more preferred.

[0052] The acid leaching process is preferably carried out under conditions in which the oxidation-reduction potential, measured with respect to the silver-silver chloride electrode, is adjusted to be between -300mV and 0mV. By adding the aforementioned oxidizing agent, the oxidation-reduction potential measured relative to the silver-silver chloride electrode can be adjusted to be between -300mV and 0mV.

[0053] --phosphoric acid-- There is no particular limit to the amount of phosphoric acid added, and it can be appropriately selected depending on the purpose. However, in terms of suppressing the inclusion of aluminum or zinc, it is preferable that the amount of phosphoric acid added is 0.1 times or more, more preferably 0.5 times or more, even more preferably 1 time or more, particularly preferably 1.5 times or more, and most preferably 1.7 times or more, relative to the total amount of impurity metals (iron, aluminum, zinc) other than valuable metals including cobalt and nickel in the raw material powder. There is no particular upper limit to the amount of phosphoric acid added, and it can be appropriately selected depending on the purpose. However, in order to suppress the inclusion of aluminum or zinc, it is preferable that the amount be 10 times or less the total amount of impurity metals other than valuable metals, including cobalt and nickel, in the raw material powder, more preferably 5 times or less, even more preferably 3 times or less, and particularly preferably 2 times or less. Furthermore, a range of values ​​where one of the values ​​indicated as the lower limit and one of the values ​​indicated as the upper limit are used as the preferred range. Among these, a molar amount of 0.1 to 10 times is preferred, a molar amount of 0.5 to 5 times is more preferred, a molar amount of 1 to 3 times is even more preferred, a molar amount of 1.5 to 3 times is particularly preferred, and a molar amount of 1.7 to 2 times is most preferred.

[0054] In this invention, examples of impurity metals include iron, aluminum, copper, and zinc, while examples of valuable metals containing cobalt and nickel include cobalt, nickel, lithium, and manganese.

[0055] There are no particular restrictions on the concentration of the phosphoric acid, and it can be appropriately selected depending on the purpose, but it is preferably 50% by mass or more and 95% by mass or less, preferably 70% by mass or more and 95% by mass or less, and more preferably 80% by mass or more and 90% by mass or less. In this specification, "phosphate" refers to orthophosphate (H3PO4).

[0056] There are no particular restrictions on the lower limit of the pH at the end of the acid leaching process, and it can be appropriately selected depending on the purpose. However, in terms of recovering cobalt and nickel with high efficiency, a pH of 0 or higher is preferable, 1.0 or higher is more preferable, 1.5 or higher is even preferable, and 1.9 or higher is particularly preferable. There are no particular restrictions on the upper limit of the pH at the end of the acid leaching process, and it can be appropriately selected depending on the purpose. However, in terms of retaining dissolved nickel and cobalt, a pH of 7.0 or less is preferred, 6.0 or less is more preferred, 5.0 or less is even more preferred, and 2.1 or less is particularly preferred. Furthermore, a range of values ​​where one of the values ​​indicated as the lower limit and one of the values ​​indicated as the upper limit are used as the preferred range. Among these, a value of 0 to 7.0 is preferred, 1.0 to 6.0 is more preferred, 1.5 to 5.0 is even more preferred, and 1.9 to 2.1 is particularly preferred.

[0057] There are no particular restrictions on the oxidation-reduction potential (ORP) at the end of the acid leaching process, and it can be appropriately selected depending on the purpose. However, in terms of recovering cobalt and nickel with high efficiency, -300mV to 0mV is preferred, -300mV to -50mV is more preferred, -300mV to -150mV is even more preferred, and -300mV to -200mV is particularly preferred. The aforementioned oxidation-reduction potential is the oxidation-reduction potential measured with respect to the silver-silver chloride electrode. The aforementioned oxidation-reduction potential can be measured, for example, using an oxidation-reduction potential measuring instrument with a silver-silver chloride electrode as the reference electrode.

[0058] -Pyrophosphoric acid mixing process- The pyrophosphate mixing step involves mixing the acid leachate obtained in the acid leaching step with a water-soluble pyrophosphate compound to obtain a pyrophosphate mixture.

[0059] --Pyrophosphate compounds-- The pyrophosphate compound is not particularly limited as long as it is water-soluble and can be appropriately selected depending on the purpose. Examples include pyrophosphate (H4P2O7), sodium pyrophosphate (Na4P2O7), monohydrogen pyrophosphate (Na3HP2O7), dihydrogen pyrophosphate (Na2H2P2O7), trihydrogen pyrophosphate (NaH3P2O7), potassium pyrophosphate (K4P2O7), monohydrogen pyrophosphate (K3HP2O7), dihydrogen pyrophosphate (K2H2P2O7), and pyrophosphate. Examples include potassium trihydrogen (KH3P2O7), lithium pyrophosphate (Li4P2O7), lithium monohydrogen pyrophosphate (Li3HP2O7), lithium dihydrogen pyrophosphate (Li2H2P2O7), lithium trihydrogen pyrophosphate (LiH3P2O7), ammonium pyrophosphate ((NH4)4P2O7), ammonium monohydrogen pyrophosphate ((NH4)3HP2O7), ammonium dihydrogen pyrophosphate ((NH4)2H2P2O7), ammonium trihydrogen pyrophosphate (NH4H3P2O7), and their hydrates. Among these, those that do not contain ammonium ions are preferred in order to prevent the formation of complexes between cobalt and nickel and ammonia, which can make recovery difficult. Sodium pyrophosphate (Na4P2O7), potassium pyrophosphate (K4P2O7), or their hydrates are even more preferred as they are readily available.

[0060] There are no particular restrictions on the lower limit of the amount of the pyrophosphate compound, and it can be appropriately selected depending on the purpose. However, in terms of suppressing copper contamination, a molar amount of 0.01 times or more the total molar amount of copper in the raw material powder is preferred, more preferably 0.05 times or more, even more preferably 0.1 times or more, particularly preferred, and most preferably 0.4 times or more the total molar amount of copper. There is no particular upper limit to the amount of the pyrophosphate compound, and it can be appropriately selected depending on the purpose. However, from the viewpoint of suppressing the cost of the pyrophosphate compound, it is preferable that the amount is 10 times or less the total amount of copper in the raw material powder, more preferably 5 times or less, even more preferably 3 times or less, particularly preferably 2 times or less, and most preferably 1 time or less. Furthermore, a range of values ​​where one of the values ​​indicated as the lower limit and one of the values ​​indicated as the upper limit are used as the preferred range. Among these, a molar amount of 0.01 to 10 times is preferred, a molar amount of 0.05 to 5 times is more preferred, a molar amount of 0.1 to 3 times is even more preferred, a molar amount of 0.4 to 2 times is particularly preferred, and a molar amount of 0.5 to 1 time is most preferred.

[0061] It is preferable to adjust the pH of the acid leachate obtained in the acid leaching step before the pyrophosphate addition step (before the addition of the pyrophosphate compound).

[0062] There are no particular restrictions on the lower limit of the pH before the pyrophosphate addition step (before the addition of the pyrophosphate compound), and it can be appropriately selected depending on the purpose. However, in terms of suppressing the decomposition of pyrophosphate, a pH of 1.0 or higher is preferred, 2.0 or higher is more preferred, 3.0 or higher is even more preferred, 3.5 or higher is particularly preferred, and 4.0 or higher is most preferred. If pyrophosphate decomposes, it becomes necessary to add a larger amount of the pyrophosphate compound to prevent a decrease in copper removal efficiency, which leads to increased costs and is therefore undesirable. There are no particular restrictions on the upper limit of the pH before the pyrophosphate addition step (before the addition of the pyrophosphate compound), and it can be appropriately selected depending on the purpose. However, in terms of maintaining the dissolution of nickel and cobalt, a pH of 10.0 or less is preferred, 7.0 or less is more preferred, 6.0 or less is even more preferred, 5.0 or less is particularly preferred, and 4.5 or less is most preferred. Furthermore, a range of values ​​where one of the values ​​indicated as the lower limit and one of the values ​​indicated as the upper limit are used as the preferred range. Among these, values ​​of 1.0 to 10.0 are preferred, values ​​of 2.0 to 7.0 are more preferred, values ​​of 3.0 to 6.0 are even more preferred, values ​​of 3.5 to 5.0 are particularly preferred, and values ​​of 4.0 to 4.5 are most preferred.

[0063] It is preferable to adjust the pH of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step.

[0064] There are no particular restrictions on the lower limit of the pH of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step, and it can be appropriately selected depending on the purpose. However, from the viewpoint of reducing the residual aluminum content, a pH of 2.0 or higher is preferred, 3.0 or higher is more preferred, and 4.0 or higher is most preferred. There are no particular restrictions on the upper limit of the pH of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step, and it can be appropriately selected depending on the purpose. However, from the viewpoint of reducing the residual aluminum content, a pH of 7.0 or less is preferred, 6.0 or less is more preferred, and 5.5 or less is most preferred. Furthermore, a range of values ​​where one of the values ​​indicated as the lower limit and one of the values ​​indicated as the upper limit are used as the preferred range. Among these, a value of 2.0 to 7.0 is preferred, 3.0 to 6.0 is more preferred, and 4.0 to 5.5 is most preferred.

[0065] It is preferable to adjust the oxidation-reduction potential (ORP) of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step.

[0066] There are no particular restrictions on the oxidation-reduction potential (ORP) at the end of the pyrophosphate addition step, and it can be appropriately selected depending on the purpose. However, in terms of suppressing iron contamination, an ORP of 0 mV to 600 mV is preferred, 50 mV to 550 mV is more preferred, 100 mV to 400 mV is even more preferred, and 200 mV to 350 mV is particularly preferred. The aforementioned oxidation-reduction potential is the oxidation-reduction potential measured with respect to the silver-silver chloride electrode. The aforementioned oxidation-reduction potential can be measured, for example, using an oxidation-reduction potential measuring instrument with a silver-silver chloride electrode as the reference electrode.

[0067] There are no particular limitations on the means used to adjust the pH and oxidation-reduction potential (ORP) before the pyrophosphate addition step (before the addition of the pyrophosphate compound) and at the end of the pyrophosphate addition step, and these can be appropriately selected depending on the purpose. Examples include adding an alkali or acid to adjust the pH, and adding an oxidizing agent to adjust the ORP.

[0068] There are no particular restrictions on the alkali, and it can be appropriately selected depending on the purpose. For example, caustic soda (sodium hydroxide) can be used. An oxidizing agent containing alkali, such as sodium hypochlorite, may also be used.

[0069] When the added caustic soda is in solution form, there are no particular restrictions on its concentration, and it can be appropriately selected depending on the purpose. However, a concentration of 10% to 70% by mass is preferred, 20% to 60% by mass is preferred, and 20% to 50% by mass is even more preferred.

[0070] The acid is not particularly limited and can be appropriately selected depending on the purpose; for example, sulfuric acid is an example.

[0071] In adjusting the pH and oxidation-reduction potential (ORP) of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step, the timing of adding alkali, acid and oxidizing agent is not particularly limited as long as the pH and oxidation-reduction potential (ORP) of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step remain within the desired range, and may be done before or after mixing the water-soluble pyrophosphate compound.

[0072] -Solid-liquid separation process- The solid-liquid separation step involves separating the pyrophosphate mixture obtained in the pyrophosphate mixing step from its solid-liquid state to obtain an aqueous solution containing cobalt and nickel.

[0073] There are no particular restrictions on the method of solid-liquid separation, and it can be appropriately selected depending on the purpose, for example, filtration.

[0074] -Other processes- Other processes mentioned above are not particularly limited and can be appropriately selected depending on the purpose. Examples include a heat treatment process, a crushing process, a first classification process, a dispersion process, a grinding process, a second classification process, a first magnetic separation process, a second magnetic separation process, and a manganese leaching process. The recovery method of the present invention can be implemented without including a solvent extraction step. In the present invention, cobalt and nickel can be recovered with high efficiency from raw material powder containing cobalt, nickel, and copper, while suppressing the inclusion of copper, without using solvent extraction, which has high equipment costs due to explosion-proof equipment and solvent costs during operation.

[0075] The raw material powder may be the heat-treated product of the lithium-ion secondary battery, the heat-treated product from which some components such as molten aluminum have been partially removed, the product recovered by performing physical separation such as crushing or classification on the heat-treated product or the heat-treated product from which some components have been partially removed, or the magnetically deposited product obtained by magnetic separation of these products. The raw material powder can be obtained by processing the lithium-ion secondary battery in any or a combination of the following steps: heat treatment, crushing, first classification, dispersion, pulverization, second classification, first magnetic separation, and second magnetic separation.

[0076] --Heat Treatment Process-- The heat treatment step is a step of heat-treating the lithium-ion secondary battery. In the heat treatment step, a heat-treated product of the lithium-ion secondary battery can be obtained. The aforementioned heat treatment is as described in the "--raw material powder--" section of the "--acid leaching process--" above.

[0077] --Crushing Process-- The crushing step is a step of obtaining crushed material by crushing the heat-treated material obtained in the heat treatment step. The aforementioned crushed material refers to material obtained by crushing heat-treated material.

[0078] The crushing process is not particularly limited as long as it is a process that crushes the heat-treated material to obtain crushed material, and can be appropriately selected according to the purpose, but it is preferable to crush the heat-treated material by impact to obtain crushed material. Furthermore, if the outer casing of the lithium-ion secondary battery does not melt during heat treatment, it is even more preferable to pre-crush the heat-treated material by cutting it with a cutting machine before applying impact to the heat-treated material.

[0079] Methods of crushing by impact include, for example, throwing the heat-treated material with a rotating impact plate and striking it against an impact plate to apply impact, or striking the heat-treated material with a rotating beater, and can be carried out by a hammer crusher, for example. Another method of crushing by impact is striking the heat-treated material with a ball made of ceramic or similar material, and this method can be carried out by a ball mill, for example. Furthermore, crushing by impact can also be carried out using, for example, a twin-shaft shredder with a short blade width and blade length that is used for crushing by compression. Furthermore, methods of crushing by impact include, for example, using two rotating chains to strike the heat-treated material and apply impact, which can be done, for example, with a chain mill.

[0080] By crushing the heat-treated material through impact, the crushing of the positive electrode current collector (e.g., aluminum (Al)) is promoted, but the negative electrode current collector (e.g., copper (Cu)), whose shape has not changed significantly, remains in a foil-like form. Therefore, in the crushing process, the negative electrode current collector is only cut, so in the first classification process (classification process) described later, it is possible to obtain crushed material in a state where valuable materials derived from the positive electrode current collector and valuable materials derived from the negative electrode current collector can be efficiently separated.

[0081] There are no particular restrictions on the crushing time in the crushing process, and it can be appropriately selected according to the purpose. However, the crushing time per 1 kg of lithium-ion secondary battery is preferably 1 second to 30 minutes, more preferably 2 seconds to 10 minutes, and particularly preferably 3 seconds to 5 minutes.

[0082] --First Classification Process-- The first classification step is a step of obtaining a coarse-grained product 1 and a fine-grained product by classifying the crushed material obtained in the crushing step.

[0083] The first classification step includes a process to obtain a coarse-grained product 1 and a fine-grained product by classifying the crushed material at a classification point of 600 μm or more and 2,400 μm or less, and it is preferable to classify at a classification point of 850 μm or more and 1,700 μm or less. The first classification step described above is not particularly limited as long as it classifies the crushed material to obtain coarse-grained product 1 (sieved product) and fine-grained product (undersieved product), and can be appropriately selected according to the purpose.

[0084] There are no particular restrictions on the classification method in the first classification step described above, and it can be appropriately selected according to the purpose. For example, it can be carried out using a vibrating screen, a multi-stage vibrating screen, a cyclone, a standard screen of JIS Z8801, a wet vibrating table, an air table, etc. Through classification, copper (Cu), iron (Fe), etc. can be separated into the coarse-grained product 1, and lithium, cobalt, nickel, or carbon can be concentrated into the fine-grained product.

[0085] In the first classification step described above, the particle size (classification point, sieve opening) is set to a classification point of 600 μm to 2,400 μm, in order to separate copper (Cu), iron (Fe), aluminum (Al), etc. into the coarse-grained product 1 and concentrate carbon (C), lithium (Li), cobalt (Co), nickel (Ni), manganese (Mn), etc. into the fine-grained product.

[0086] When using a sieve as the classification method, by placing, for example, stainless steel balls or alumina balls on the sieve as a crushing accelerator and performing the classification, smaller crushed material adhering to larger crushed material can be separated from the larger crushed material. This allows for more efficient separation of large and small crushed material, further improving the quality of the recovered metal.

[0087] In the first classification step described above, the crushing process can also be carried out simultaneously with the classification process. For example, the heat-treated material obtained in the heat treatment step may be crushed, and the crushed material may be classified into coarse-grained product 1 and fine-grained product in a crushing and classification step (crushing and classification). If the proportion of fine-grained products is low in the first classification process (classification treatment), the coarse-grained product 1 can be returned to the process of crushing the heat-treated material.

[0088] --Dispersion process-- The dispersion step involves immersing the fine-grained product obtained after the first classification step in water (dispersion treatment) to obtain an aqueous dispersion of the fine-grained product, which is a slurry-like liquid (fine-grained product slurry). In the grinding process described later, if wet grinding is performed, it is preferable to perform the dispersion process described above.

[0089] The aforementioned dispersion process is not particularly limited as long as it involves immersing (soaking, placing in water) the fine-grained product recovered in the first classification process in water to disperse the fine-grained product in water and obtain a slurry (suspension). It can be appropriately selected according to the purpose.

[0090] There are no particular restrictions on the dispersion medium used to disperse the fine-grained product, and it can be appropriately selected depending on the purpose. Examples include pure water such as industrial water, tap water, ion-exchanged water, ultrafiltered water, reverse osmosis water, and distilled water, as well as ultrapure water.

[0091] There are no particular restrictions on the dispersion method, and it can be appropriately selected depending on the purpose. Examples include simply placing the granular product in water, placing the granular product in water and stirring, placing the granular product in water and stirring while applying ultrasonic waves, and adding water to the granular product. Among these, the method of placing the granular product in water and stirring is preferred, and the method of placing the granular product in water and stirring while applying ultrasonic waves is more preferred.

[0092] There are no particular restrictions on the solid-liquid ratio (concentration (mass ratio) of the fine-grained product to water) in the dispersion treatment described above, and it can be appropriately selected according to the purpose, but it is preferably 1% by mass or more and 50% by mass or less, and more preferably 5% by mass or more and 30% by mass or less. If the solid-liquid ratio is less than 1% by mass, cobalt and nickel, which would normally be recovered as magnetic deposits, will not be recovered by the magnetic separator and will be lost to non-magnetic deposits, which is likely to reduce the recovery rate of cobalt and nickel. If the solid-liquid ratio exceeds 50% by mass, the amount of impurities trapped in the magnetic material increases, which may lead to a decrease in cobalt and nickel content.

[0093] There are no particular restrictions on the stirring speed of the water in the dispersion treatment described above, and it can be appropriately selected according to the purpose, for example, it can be set to 400 rpm. There are no particular restrictions on the leaching time in the aforementioned distributed processing; it can be appropriately selected depending on the purpose, for example, it can be 1 hour.

[0094] --Grinding Process-- The aforementioned grinding process is a step of grinding the fine granular product to obtain a pulverized material of a predetermined size.

[0095] There are no particular restrictions on the grinding method, and it can be appropriately selected depending on the purpose. For example, it can be carried out using a media-agitating grinder that uses a medium such as iron balls (attritor, bead mill, tower mill), a roller mill, a jet mill, a high-speed rotary grinder (hammer mill, pin mill), or a container-driven mill (rotary mill, vibratory mill, planetary mill).

[0096] The aforementioned grinding process can be either wet or dry, and can be appropriately selected depending on the purpose, but the wet process is preferred. By performing the grinding process in a wet manner, the decrease in the recovery rate of cobalt (Co) and nickel (Ni) due to dust generation at each step can be suppressed, and measures to prevent dust dispersion into the surrounding atmosphere become unnecessary.

[0097] The particle size (90% particle size) of the pulverized material is preferably 1,000 μm or less, more preferably 750 μm or less, and particularly preferably 500 μm or less. The 90% particle size is, for example, the particle size that accounts for 90% of the integrated particle size distribution obtained by measuring with a laser diffraction scattering particle size distribution analyzer.

[0098] The number average particle size of at least one or both of the cobalt and nickel contained in the pulverized material is preferably 100 μm or less, more preferably 75 μm or less, and particularly preferably 50 μm or less. The aforementioned number-average particle size is, for example, the average value calculated by measuring the particle sizes of a total of 100 cobalt and nickel particles using electron microscopy.

[0099] A smaller 90% particle size or number-average particle size promotes the separation of cobalt and nickel from other components, thereby improving the cobalt and nickel quality of magnetic deposits 1 and 2 recovered in the first and second magnetic separation processes described below. Even if the 90% particle size or number-average particle size is small, the recovery rate of cobalt and nickel in the first and second magnetic separation processes can be increased, so further recovery processes such as a third magnetic separation process may be provided as needed.

[0100] --Second Classification Process-- The second classification step is a step in which the pulverized material obtained in the pulverization step is classified at a classification point smaller than the classification point of the first classification step, thereby obtaining a coarse-grained product 2 and a fine-grained product.

[0101] In the second classification step, the pulverized material is classified at a classification point smaller than that of the first classification step, and between 75 μm and 1,200 μm, thereby obtaining a coarse-grained product 2 and a fine-grained product. For example, when the second classification step is performed using a JIS Z8801 standard sieve with a classification point of 500 μm, the product on the sieve surface of the standard sieve with a classification point of 500 μm is the coarse-grained product 2, and the product below the sieve surface is the fine-grained product. Copper can be concentrated and recovered from the coarse-grained product 2.

[0102] The classification point used in the second classification step is preferably 25 μm to 1,700 μm, more preferably 75 μm to 1,200 μm, even more preferably 75 μm to 850 μm, and particularly preferably 106 μm to 600 μm. If the classification point exceeds 1,700 μm, the inclusion of copper in the fine-grained product increases, and the cobalt and nickel grades may decrease. If the classification point falls below 25 μm, the grinding energy required to recover cobalt and nickel in the fine-grained product may become excessive.

[0103] There are no particular restrictions on the classification method in the second classification step described above, and it can be appropriately selected according to the purpose. For example, it can be carried out using a vibrating screen, a multi-stage vibrating screen, a cyclone, a standard screen of JIS Z8801, a wet vibrating table, an air table, etc. The second classification step described above is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable to perform it wet. When wet classification is performed, the aqueous dispersion of the pulverized material obtained from the wet pulverization process may be supplied as is, or a dispersion medium (water) may be added to the aqueous dispersion of the pulverized material to dilute it and adjust the solid-liquid ratio.

[0104] When the second classification process is carried out in a wet manner and a vibrating screen or a multi-stage vibrating screen is used, showering the top of the screen with a dispersion medium (water) suppresses the aggregation of the pulverized material during classification, thereby obtaining good classification results.

[0105] The phase angle of the weight of the vibrating screen is preferably 30° to 90°, more preferably 40° to 80°, and particularly preferably 50° to 70°. By setting the phase angle to this value, excessive discharge of crushed material and classified products outside the screening device (insufficient residence time on the screen) can be prevented, and good classification results can be obtained.

[0106] --First Magnetic Separation Process-- The first magnetic separation step is a step in which the fine-grained product obtained in the second classification step is magnetically separated to obtain magnetically attached material 1 and non-magnetically attached material 1.

[0107] The magnetic object 1 refers to an object that, due to the magnetic force generated by a magnetic source (for example, a magnet or electromagnet), generates an attractive force between itself and the magnetic source and can be attracted to the magnetic source. Examples of the magnetic material 1 include ferromagnetic metals. Examples of ferromagnetic metals include iron (Fe), nickel (Ni), and cobalt (Co).

[0108] The non-magnetic material 1 refers to a material that is not attracted to the magnetic source by the magnetic force generated by the magnetic source. There are no particular restrictions on the non-magnetic material, and it can be selected according to the purpose. Examples of non-magnetic metals include paramagnetic or semimagnetic metals. Examples of paramagnetic or semimagnetic metals include aluminum (Al), manganese (Mn), gold (Au), silver (Ag), and copper (Cu).

[0109] The first magnetic separation step may be either dry magnetic separation or wet magnetic separation, but wet magnetic separation is preferred for the following reasons. When magnetically separating the fine particles obtained in the second classification step, for example, if dry magnetic separation is performed, particle aggregation may occur due to moisture adhering between particles, and it may not be possible to sufficiently separate the metal particles derived from the negative electrode current collector and the fine particles of the negative electrode active material, cobalt particles, and nickel particles that are present in the fine particles at a concentration of 10% by mass or more in the fine particles. For this reason, it is preferable to perform wet magnetic separation to separate the material derived from the negative electrode active material and the metal derived from the negative electrode current collector into a non-magnetic slurry, and to recover the cobalt and nickel as magnetic material 1.

[0110] In the wet magnetic separation process, the aqueous dispersion of the fine particles obtained in the second wet classification step may be supplied as is, or the aqueous dispersion of the fine particles may be concentrated or diluted by solid-liquid separation such as sedimentation separation to adjust the solid-liquid ratio. Alternatively, the solid-liquid ratio may be adjusted by adding water to the slurry of the fine particles to dilute it.

[0111] There are no particular restrictions on the solid-liquid ratio (concentration (mass ratio) of the fine product relative to water) of the slurry supplied to the wet magnetic separator, and it can be appropriately selected according to the purpose, but it is preferably 5% by mass or more and 67% by mass or less, and more preferably 10% by mass or more and 40% by mass or less. If the solid-liquid ratio is less than 5% by mass, the recovery rate of cobalt and nickel as magnetic deposits in the wet magnetic separator may decrease. When the solid-liquid ratio exceeds 67% by mass, problems such as pump blockage during slurry supply are likely to occur, and the separation performance of cobalt and nickel (magnetic materials) from non-magnetic materials such as carbon may decrease.

[0112] There are no particular restrictions on the method of supplying the aqueous dispersion, and it can be appropriately selected according to the purpose, but it may also be supplied by pumping while stirring the aqueous dispersion in the tank.

[0113] There are no particular restrictions on the magnetic separation method in the first magnetic separation step, and it can be carried out using a known magnetic separator (magnetic separator), for example, a drum-type magnetic separator or a high-gradient magnetic separator. Among these, the method using a drum-type magnetic separator is preferred.

[0114] The magnetic flux density for magnetic separation in the first magnetic separation step is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.05T or more and 0.9T or less, more preferably 0.075T or more and 0.6T or less, still preferably 0.1T or more and less than 0.3T, and particularly preferably 0.1T or more and 0.2T or less. If the magnetic flux density is less than 0.05T, it becomes difficult to magnetically attach cobalt and nickel fine particles, and the recovery rate of cobalt and nickel in the magnetically attached material tends to decrease. When the magnetic flux density exceeds 0.9T, the recovery rate of impurities other than cobalt and nickel into the magnetic deposit 1 increases, which may lead to a decrease in the cobalt and nickel content in the magnetic deposit 1.

[0115] Examples of drum-type wet magnetic separation methods in the first magnetic separation process include: (1) as shown in Figure 1, a magnet is placed at the 6 o'clock position on the drum, a non-magnetic slurry is introduced from the 3 o'clock position (side), and the drum is rotated clockwise; and (2) as shown in Figure 2, a magnet is placed near the 3 o'clock position on the drum, a non-magnetic slurry is introduced from the 12 o'clock to 2 o'clock position (top) of the drum, and the drum is rotated counterclockwise. Among these methods, (1) the drum-type wet magnetic separation method shown in Figure 1 is preferred because it yields high-quality magnetic deposits of cobalt and nickel.

[0116] --Second Magnetic Separation Process-- The second magnetic separation step is a step in which the non-magnetic material 1 obtained in the first magnetic separation step is magnetically separated to obtain magnetic material 2 and non-magnetic material 2. If the second magnetic separation step recovers dust generated during the transfer of the fine-grained product obtained in the first classification step, the collected dust can also be included as the target of magnetic separation.

[0117] The combined grade of cobalt and nickel contained in the non-magnetic material 1 obtained in the first magnetic separation step is preferably 30% by mass or less, more preferably 20% by mass or less, and particularly preferably 15% by mass or less. Even if the non-magnetic material 1 has a combined cobalt and nickel content of 30% by mass or less, it can be recovered as magnetic material in the second magnetic separation process, thereby improving the recovery rate of cobalt and nickel. However, it is a well known fact that the higher the cobalt and nickel content of the non-magnetic material, the easier it is to recover cobalt and nickel into the magnetic material.

[0118] The number average particle size of at least one of the cobalt and nickel contained in the non-magnetic material 1 obtained in the first magnetic separation step is preferably 50 μm or less, more preferably 35 μm or less, and particularly preferably 25 μm or less. The aforementioned number-average particle size is, for example, the average value calculated by measuring the particle sizes of a total of 100 cobalt and nickel particles using electron microscopy. A smaller number-average particle size promotes the separation of cobalt and nickel from other components, thereby improving the cobalt and nickel quality of the magnetically deposited material 2 recovered in the second magnetic separation step. Furthermore, since the recovery rate of cobalt and nickel in the second magnetic separation step can be increased, a third magnetic separation step or other further recovery steps may be provided as needed. Even cobalt and nickel particles with an average particle size of 50 μm or less can be recovered as magnetically deposited material in the second magnetic separation step, thereby improving the recovery rate of cobalt and nickel throughout the entire process.

[0119] There are no particular restrictions on the magnetic separation method in the second magnetic separation step, and it can be carried out using a known magnetic separator (magnetic separator), for example, a drum-type magnetic separator or a high-gradient magnetic separator.

[0120] The magnetic flux density for magnetic separation in the second magnetic separation step is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.3T or more and 2T or less, more preferably 0.4T or more and 1.8T or less, and particularly preferably 0.6T or more and 1.2T or less. If the magnetic flux density is less than 0.3T, it becomes difficult to magnetically attach cobalt and nickel fine particles, and the recovery rate of cobalt and nickel in the magnetically attached material tends to decrease. When the magnetic flux density exceeds 2T, the recovery rate of impurities other than cobalt and nickel into the magnetic deposit 2 increases, which may lead to a decrease in the cobalt and nickel content in the magnetic deposit 2.

[0121] The second magnetic separation step is preferably carried out by wet magnetic separation. As for the wet magnetic separation method, a method using a high-gradient wet magnetic separation method or a drum-type wet magnetic separation method is preferred.

[0122] The aforementioned high-gradient wet magnetic separation method can be repeated two or more times. In the aforementioned high-gradient wet magnetic separation method, it is preferable to use a matrix in order to increase the change in magnetic flux density. As the aforementioned matrix, for example, a horizontal iron matrix (line width: 2 mm, thickness: 4 mm, width 200 mm x height 50 mm) shown in Figure 3A and a vertical iron matrix (maximum rhombus length: 22 mm, minimum rhombus length: 10 mm, thickness: 4 mm, width 200 mm x height 50 mm) shown in Figure 3B can be used. A matrix member (width 200 mm x height 50 mm x thickness: 28 mm) shown in Figure 4 can be used, which is formed by alternately stacking and bundling three horizontal matrices from Figure 3A and four vertical matrices from Figure 3B.

[0123] Examples of the aforementioned drum-type wet magnetic separation method include a method in which a non-magnetic material slurry is introduced into a rotating drum having a magnet. There are no particular restrictions on the direction of rotation; it can be selected as appropriate depending on the purpose, and it may be clockwise or counterclockwise. There are no particular restrictions on the position of the magnet in the drum, and it can be appropriately selected according to the purpose. For example, it may be in the same position as the input position for the non-magnetic slurry, or it may be in a different position from the input position for the non-magnetic slurry.

[0124] Specific examples of the drum-type wet magnetic separation method include, for example, (1) as shown in Figure 1, a magnet is placed at the 6 o'clock position on the drum, a non-magnetic slurry is introduced from the 3 o'clock position (side), and the drum is rotated clockwise; and (2) as shown in Figure 2, a magnet is placed near the 3 o'clock position on the drum, a non-magnetic slurry is introduced from the vicinity of the 12 o'clock to 2 o'clock position (top) on the drum, and the drum is rotated counterclockwise. Among these, the drum-type wet magnetic separation method shown in Figure 2 (2) is preferred because it yields high recovery rates for cobalt and nickel. In the method described in Figure 2 (2), the magnetic material attracted to the magnet is carried in the 9 o'clock direction by the rotation of the drum and recovered, while the non-magnetic material slurry flows along the drum surface in the 3 o'clock to 6 o'clock direction and is discharged from the 6 o'clock direction.

[0125] The second magnetic separation step can be carried out by adding a dispersant to the non-magnetic slurry obtained in the first magnetic separation step. By adding a dispersant to the non-magnetic slurry, the magnetic separation efficiency of the second magnetic separation step can be improved. There are no particular restrictions on the dispersant, and it can be appropriately selected depending on the purpose. For example, dispersants used in the fields of dyes, pigments, pesticides, and inorganic materials can be used. Examples of the dispersant include a condensate of aromatic sulfonic acid and formalin, and an anionic surfactant mainly composed of a special carboxylic acid type polymer surfactant (for example, the surfactants in the "Demol" series manufactured by Kao Corporation).

[0126] Additional magnetic separation may be performed on the magnetic material 1 and magnetic material 2 or either thereof, and additional magnetic separation may be performed on the non-magnetic material 1 and non-magnetic material 2 or either thereof.

[0127] The combined cobalt and nickel content in the magnetically deposited material obtained by the wet magnetic separation method is preferably concentrated to 1.3 times or more, and more preferably to 1.5 times or more, than the combined cobalt and nickel content in the fine-grained product.

[0128] Solid-liquid separation may be performed on the magnetically deposited material obtained by the wet magnetic separation method described above. There are no particular restrictions on the solid-liquid separation method, and it can be appropriately selected according to the purpose. For example, a solid-liquid separation method using a filter press can be used.

[0129] -Manganese leaching process- The manganese leaching process involves adding acid to a slurry containing raw material powder and water. After adding acid, solid-liquid separation can be performed to obtain manganese leachate and solid components (cobalt-nickel residue). [Examples]

[0130] The following describes embodiments of the present invention, but the present invention is not limited in any way to these embodiments.

[0131] <Manufacturing of raw material powders> (Manufacturing example) -Heat treatment process- The waste lithium-ion secondary batteries (approximately 300 kg) to be processed were subjected to heat treatment using a batch-type burner furnace from Ecosystem Akita Co., Ltd. as the heat treatment device. The heat treatment was performed at a temperature of 750°C (heating up from 20°C to 750°C over 15 minutes, then holding for 3 hours) under air conditions to obtain a heat-treated product.

[0132] -Crushing Process- Next, a chain mill (cross-flow shredder S-1000, manufactured by Sato Iron Works Co., Ltd.) was used as a crushing device to crush the heat-treated lithium-ion secondary batteries under conditions of 50Hz (chain tip speed: approximately 60m / sec) and residence time of 50 seconds, thereby obtaining the crushed lithium-ion secondary battery material.

[0133] -First Classification Process- Next, the crushed lithium-ion secondary battery material was sieved using a vibrating sieve with a mesh size of 1.2 mm (200 mm in diameter, manufactured by Tokyo Screen Co., Ltd.). After sieving, the 1.2 mm sieved product (coarse-grained product 1) and the unsieved product (fine-grained product) were collected separately. The cobalt grade of the fine-grained product (black mass) was 6.2 mass%, the nickel grade was 13.5 mass%, and the combined grade was 19.7 mass%.

[0134] -Dispersion process- The obtained 62.5 kg of fine-grained product was immersed in 250 L of water and dispersed under conditions of a solid-liquid ratio of 25% by mass, a stirring speed of 400 rpm, and a leaching time of 1 hour to obtain an aqueous dispersion of the fine-grained product.

[0135] -Wet grinding process- The obtained fine-grained product aqueous dispersion and 10 kg of grinding medium (iron balls) were used with a medium-agitating type grinder (tower mill NE008, manufactured by Nippon Eirich Co., Ltd.). The aqueous dispersion of the fine-grained product was supplied in 20 portions, and wet grinding was performed for 30 minutes at a rotation speed of 716 rpm (peripheral speed of 3 m / sec) per portion.

[0136] -Second Classification Process- Next, the aqueous dispersion of the fine-grained product obtained by wet grinding was subjected to wet classification using JIS Z8801 standard sieves with mesh sizes of 500 μm and 250 μm. The product on the 500 μm sieve (coarse-grained product 2) and the product below the 250 μm sieve (aqueous dispersion of fine-grained product) were collected separately. The intermediate product generated on the 250 μm sieve was returned to the previous wet grinding process and ground repeatedly until it all passed through the 250 μm sieve.

[0137] -First Magnetic Separation Process- The obtained aqueous dispersion of fine particulate products (dispersion concentration 15% by mass) was subjected to a first magnetic separation process using a drum-type wet magnetic separator (manufactured by Elise Magnetics Co., Ltd., model: WD L-8 lab model) shown in Figure 1, with a magnetic flux density of 0.15 T and a drum rotation speed of 40 rpm, to recover the magnetically attached material 1 and the non-magnetic aqueous dispersion 1.

[0138] The drum-type wet magnetic separator shown in Figure 1 is a device in which a magnet is positioned at the 6 o'clock position on the drum, a water dispersion of fine particulate matter is introduced from the 3 o'clock position (side) of the drum, and magnetic separation is performed while the drum rotates clockwise.

[0139] For the obtained non-magnetic aqueous dispersion 1, the particle sizes of a total of 100 cobalt and nickel particles were measured by electron microscopy, and the number-average particle size was found to be 10 μm. Furthermore, the cobalt content of the non-magnetic material 1 contained in the non-magnetic aqueous dispersion 1 was 3.4 mass%, and the nickel content was 8.2 mass%, for a total content of 11.6 mass%.

[0140] Solid-liquid separation was performed on the magnetic material 1 using a filter press (PF-3C25c-20, manufactured by Nippon Filtration Equipment Co., Ltd.), and the resulting recovered material was used as raw material powder.

[0141] In the solid-liquid separation using the filter press described above, the filter plate was closed and tightened to 11 MPa using a manual hydraulic pump, and the slurry liquid of the magnetic material 1 was pumped at a pressure of 0.4 MPa for filtration. After that, it was compressed at 0.4 MPa for about 30 minutes, and air blowing was performed at 0.6 MPa for about 15 minutes. After that, the tightening was released and the plate was opened.

[0142] Compositional analysis of the obtained raw material powder using an ICP emission spectrometer (ICP-OES) revealed that the cobalt content was 11 mass%, the nickel content was 49 mass%, the copper content was 1 mass%, the iron content was 0.5 mass%, the aluminum content was 4.4 mass%, and the zinc content was 0.1 mass%.

[0143] <Recovery of cobalt and nickel> A 1L beaker was used as the container, and various operations were performed while stirring with a stirring blade at a liquid temperature of 40°C and a rotation speed of 400 rpm.

[0144] (Example 1) Cobalt and nickel were recovered from the raw material powder according to the flow shown in Figure 5.

[0145] -Acid leaching process- A raw material slurry was prepared by adding 398 g of pure water to 102 g of the raw material powder (black mass magnetized material) obtained in the above manufacturing example.

[0146] To the raw material slurry, 98% by mass concentrated sulfuric acid (sulfuric acid, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added as an acid to achieve a pH of 2.0. Subsequently, sodium hypochlorite (12% by mass available chlorine, manufactured by Kanto Denka Kogyo Co., Ltd.) (the same applies hereafter) was added as an oxidizing agent to achieve an ORP of -200mV. Thereafter, concentrated sulfuric acid and sodium hypochlorite were added as appropriate to maintain the slurry's pH at 1.9 to 2.1 and its ORP at -300mV to 0mV, and the pH and ORP of the slurry were maintained within the above range for 240 minutes from the start of adding concentrated sulfuric acid to obtain an acid leaching slurry. pH and oxidation-reduction potential (ORP) were measured using a pH / ORP meter (Horiba, Ltd., F-73) (the same method was used for the following measurements).

[0147] -Pyrophosphoric acid addition process- Sodium hypochlorite was added to the acid-leached slurry until the pH rose to 4.0. Next, sodium pyrophosphate decahydrate (sometimes referred to as sodium pyrophosphate) was added in a molar amount equal to 1.1 times the molar amount of copper contained in the raw material powder. After adding sodium pyrophosphate, sodium hypochlorite was added so that the ORP of the slurry reached 300 mV. Next, 98% concentrated sulfuric acid was added so that the pH of the slurry reached 4.7. Then, sodium hypochlorite and 98% concentrated sulfuric acid were added as appropriate so that the pH of the slurry was maintained between 4.5 and 5.0 and the ORP of the slurry was maintained between 200 mV and 350 mV. The pH and ORP of the slurry were maintained within the above range for 120 minutes from the start of sodium hypochlorite addition to obtain a pyrophosphate mixture.

[0148] -Solid-liquid separation process- The slurry obtained in the pyrophosphate addition step was filtered, and the cobalt-nickel leaching solution was recovered. The composition (concentrations of various metals) of the recovered cobalt-nickel leaching solution was measured using an ICP emission spectrometer (ICP-OES). The leaching rates of nickel (Ni), cobalt (Co), and manganese (Mn), and the remaining rates of iron (Fe), aluminum (Al), copper (Cu), and zinc (Zn), calculated from the content of the raw material powder, are shown in Table 1. In Table 1, the amount of phosphoric acid added is the molar ratio to the molars of iron, aluminum, and zinc contained in the raw material powder, the amount of pyrophosphate added is the molar ratio to the molars of copper contained in the raw material powder, and the leaching rate and residual rate are the amounts in the cobalt-nickel aqueous solution after solid-liquid separation relative to the amount in the raw material powder.

[0149] [Table 1]

[0150] (Comparative Example 1) Except for the absence of sodium hypochlorite addition until the pH rose to 4.0 and the addition of sodium pyrophosphate in the pyrophosphate addition step, the cobalt-nickel leachate was collected in the same manner as in Example 1, and the composition (concentration of various metals) of the collected cobalt-nickel leachate was measured. The leaching rates of nickel (Ni), cobalt (Co), and manganese (Mn) and the remaining rates of iron (Fe), aluminum (Al), copper (Cu), and zinc (Zn), calculated from the content of the raw material powder, are shown in Table 1.

[0151] (Comparative Example 2) In the acid leaching process, an 85% by mass phosphoric acid solution was added to the slurry 240 minutes after the start of concentrated sulfuric acid addition to obtain an acid leaching solution, in an amount equal to 1.2 times the total molar amount of iron, aluminum, and zinc contained in the raw material powder. In the pyrophosphate addition process, sodium hypochlorite was not added until the pH rose to 4.0, and sodium pyrophosphate was not added. Except for these differences, the cobalt-nickel leaching solution was recovered in the same manner as in Example 1, and the composition (concentrations of various metals) of the recovered cobalt-nickel leaching solution was measured. The leaching rates of nickel (Ni), cobalt (Co), and manganese (Mn) and the remaining rates of iron (Fe), aluminum (Al), copper (Cu), and zinc (Zn), calculated from the content of the raw material powder, are shown in Table 1.

[0152] (Example 2) Cobalt and nickel were recovered from the raw material powder according to the flow shown in Figure 6.

[0153] -Manganese leaching process- A slurry was obtained by adding 2985g of pure water to 765g of the raw material powder obtained in the manufacturing example. To the obtained slurry, 47% by mass sulfuric acid (prepared using 98% concentrated sulfuric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)) was added as an acid to achieve a pH of 2.0 (the same applies hereafter). Next, 47% by mass sulfuric acid was added as needed to maintain the slurry's pH between 1.9 and 2.1, and the slurry was held for 15 minutes without adding 47% by mass sulfuric acid until the pH fluctuation range of the slurry was 0.1 or less. The solid component was obtained by solid-liquid separation of the slurry obtained after holding.

[0154] -Acid leaching process- 83 g of solids obtained in the manganese leaching process were mixed with 267 g of pure water to prepare a raw material slurry.

[0155] To the raw material slurry, 47% by mass sulfuric acid was added as an acid to achieve a pH of 2.0. Then, sodium hypochlorite was added as an oxidizing agent to achieve an ORP of -200 mV. Subsequently, 47% by mass sulfuric acid and sodium hypochlorite were added as needed to maintain the slurry's pH between 1.9 and 2.1, and its ORP between -300 mV and 0 mV, until the slurry's pH and ORP were maintained within the above ranges for 240 minutes from the start of adding the 47% by mass sulfuric acid, thereby obtaining the slurry.

[0156] To the obtained slurry, 85% by mass of phosphoric acid was added in a molar amount equal to 1.8 times the total amount of impurity metals (iron, aluminum, zinc) contained in the raw material powder, to obtain an acid leaching slurry.

[0157] -Pyrophosphoric acid addition process- Sodium hypochlorite was added to the acid-leached slurry until the pH rose to 4.0, and then sodium pyrophosphate decahydrate was added in a molar amount equal to 0.5 times the copper content in the raw material powder. Next, 98% concentrated sulfuric acid was added to bring the slurry pH to 4.7. Then, sodium hypochlorite and 47% sulfuric acid were added as appropriate to maintain the slurry pH between 4.5 and 5.0 and the slurry ORP between 200mV and 350mV, and the slurry pH and ORP were maintained within the above range for 120 minutes from the start of sodium hypochlorite addition to obtain a pyrophosphate mixture.

[0158] -Solid-liquid separation process- The slurry obtained in the pyrophosphate addition step was filtered, and the cobalt-nickel leaching solution was recovered. The composition (concentrations of various metals) of the recovered cobalt-nickel leaching solution was measured using an ICP emission spectrometer (ICP-OES). The leaching rates of nickel (Ni), cobalt (Co), and manganese (Mn), and the remaining rates of iron (Fe), aluminum (Al), copper (Cu), and zinc (Zn), calculated from the content of the raw material powder, are shown in Table 1.

[0159] (Example 3) In the acid leaching process, the mass of solids obtained in the manganese leaching process was set to 95g and the mass of pure water to 315g. Furthermore, 85% phosphoric acid was added to the slurry 240 minutes after the start of adding 47% sulfuric acid, in a molar amount equal to 1.5 times the total amount of impurity metals (iron, aluminum, zinc) contained in the raw material powder. Except for these differences, the cobalt-nickel leaching solution was recovered in the same manner as in Example 2, and the composition (concentrations of various metals) of the recovered cobalt-nickel leaching solution was measured. Table 1 shows the leaching rates of nickel (Ni), cobalt (Co), and manganese (Mn), and the remaining rates of iron (Fe), aluminum (Al), copper (Cu), and zinc (Zn), calculated from the raw material powder content.

[0160] (Example 4) The following were performed: 98% concentrated sulfuric acid was used instead of 47% sulfuric acid throughout the entire process; in the manganese leaching process, the mass of raw material powder was 128g and the mass of pure water was 498g; in the acid leaching process, the mass of solids obtained in the manganese leaching process was 90g and the mass of pure water was 360g; and 85% phosphoric acid was added to the slurry 240 minutes after the start of sulfuric acid addition, in a molar amount equal to 1.1 times the total amount of impurity metals (iron, aluminum, zinc) contained in the raw material powder. Except for adding sodium pyrophosphate decahydrate in a molar amount equal to 0.2 times the copper content in the raw material powder during the pyrophosphate mixing process, the cobalt-nickel leaching solution was collected in the same manner as in Example 2, and the composition (concentrations of various metals) of the collected cobalt-nickel leaching solution was measured. The leaching rates of nickel (Ni), cobalt (Co), and manganese (Mn) and the remaining rates of iron (Fe), aluminum (Al), copper (Cu), and zinc (Zn), calculated from the content of the raw material powder, are shown in Table 1.

[0161] (Comparative Example 3) In the manganese leaching process, the mass of raw material powder was set to 1020g and the mass of pure water to 3980g. In the acid leaching process, the mass of solids obtained in the manganese leaching process was set to 80g and the mass of pure water to 422g. In the pyrophosphate addition process, sodium hypochlorite was not added until the pH rose to 4.0, and sodium pyrophosphate was not added. In all other cases, the cobalt-nickel leaching solution was recovered in the same manner as in Example 4, and the composition (concentration of various metals) of the recovered cobalt-nickel leaching solution was measured. The leaching rates of nickel (Ni), cobalt (Co), and manganese (Mn) and the remaining rates of iron (Fe), aluminum (Al), copper (Cu), and zinc (Zn), calculated from the raw material powder content, are shown in Table 1.

[0162] (Example 5) Solid content was obtained using the same procedure as the manganese leaching process in Example 2.

[0163] -Acid leaching process- 59 g of solids obtained were mixed with 391 g of pure water to prepare the raw material slurry. To the raw material slurry, 47% by mass sulfuric acid was added as an acid to achieve a pH of 2.0. Subsequently, air was blown into the liquid at a flow rate of 0.5 L / min as an oxidizing agent. While continuing to blow air at a flow rate of 0.5 L / min, 47% by mass sulfuric acid was added as needed to maintain the slurry's pH between 1.9 and 2.1, and the slurry's pH was maintained within this range for 240 minutes from the start of adding the 47% by mass sulfuric acid until the slurry was obtained. During this time, the ORP of the slurry remained between -300 mV and 0 mV from the start of blowing air into the liquid until the slurry was obtained. To the obtained slurry, 85% by mass of phosphoric acid was added in a molar amount equal to 1.8 times the total amount of impurity metals (iron, aluminum, zinc) contained in the raw material powder, to obtain an acid leaching slurry.

[0164] -Pyrophosphoric acid addition process- To the acid leaching slurry, a 24% by mass aqueous sodium hydroxide solution (prepared using 48% by mass caustic soda (manufactured by Takasugi Pharmaceutical Co., Ltd.)) was added until the pH rose to 4.0. Then, sodium pyrophosphate decahydrate was added in a molar amount equal to 0.5 times the copper content in the raw material powder. Next, 47% by mass sulfuric acid was added to bring the pH of the slurry to 4.7. Next, air was blown into the liquid at a flow rate of 0.5 L / min as an oxidizing agent. Then, 47% by mass sulfuric acid was added as needed to maintain the pH of the slurry between 4.5 and 5.0, and the blowing of air at a flow rate of 0.5 L / min was continued. The pH of the slurry was maintained within the above range for 120 minutes from the start of air blowing to obtain a pyrophosphate mixture. During the air blowing, the ORP of the slurry was maintained between 0 mV and 100 mV, and the ORP of the obtained pyrophosphate mixture was 86 mV.

[0165] -Solid-liquid separation process- The pyrophosphate mixture obtained in the pyrophosphate addition step was filtered, and the cobalt-nickel leaching solution was recovered. The composition (concentrations of various metals) of the recovered cobalt-nickel leaching solution was measured, and the leaching rates of nickel (Ni), cobalt (Co), and manganese (Mn), as well as the remaining rates of iron (Fe), aluminum (Al), copper (Cu), and zinc (Zn), calculated from the content of the raw material powder, are shown in Table 1.

[0166] The results in Table 1 show that by mixing the acid leaching solution obtained in the acid leaching process with a water-soluble pyrophosphate compound, the recovery rates of cobalt and nickel can be maintained at a high level while the contamination of copper can be reduced. Furthermore, it was found that adding phosphoric acid after mixing the slurry with the acid during the acid leaching process could reduce the contamination of aluminum and zinc.

Claims

1. A recovery method for recovering cobalt and nickel from raw material powder containing cobalt, nickel, and copper, An acid leaching process involves mixing a slurry containing cobalt, nickel, and copper raw material powders and water with an acid to obtain an acid leaching solution. A pyrophosphate mixing step involves mixing the acid leachate obtained in the acid leaching step with a water-soluble pyrophosphate compound to obtain a pyrophosphate mixture. A recovery method characterized by comprising a solid-liquid separation step, in which the pyrophosphate mixture obtained in the pyrophosphate mixing step is subjected to solid-liquid separation to obtain an aqueous solution containing cobalt and nickel.

2. The recovery method according to claim 1, wherein, prior to the pyrophosphate addition step, the pH of the acid leachate obtained in the acid leaching step is adjusted to 2.0 or more and 7.0 or less.

3. The recovery method according to claim 1 or 2, wherein the raw material powder contains iron.

4. The recovery method according to claim 3, wherein the oxidation-reduction potential of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step is adjusted to 0 mV or more and 600 mV or less, measured with reference to a silver-silver chloride electrode.

5. The recovery method according to claim 1 or 2, wherein the raw material powder contains at least one of aluminum and zinc.

6. The recovery method according to claim 5, wherein the pH of the pyrophosphate mixture obtained at the end of the pyrophosphate addition step is adjusted to be between 2.0 and 7.

0.

7. The recovery method according to claim 5, wherein, in the acid leaching step, phosphoric acid is added after mixing the slurry with the acid to obtain the acid leaching solution.

8. The recovery method according to claim 1 or 2, wherein the raw material powder is a magnetic material obtained by classifying and wet magnetic separation of a heat-treated lithium-ion secondary battery.

9. The recovery method according to claim 1 or 2, wherein the acid leaching step is performed under conditions in which the oxidation-reduction potential measured with respect to a silver-silver chloride electrode is -300 mV or more and 0 mV or less.

Citation Information

Patent Citations

  • Method for recovering metal from lithium-ion battery waste

    JP2023100269A